Técnicas ópticas para investigação de escoamentos multifásicos - Vendruscolo, Tiago Piovesan (2016)
Multiphase flows are present in many processes of nature as well as in industrial activities for instance in chemical reactors, power generation plants, as well as in exploration, production and transportation of oil and gas. In oil production, a mixture of two or more phases composed by oil, gas and/or water is commonly found. Such multiphase mixtures stream in pipes and equipment assuming different patterns with different spatial configurations. In numerous situations, flow behavior determines the efficiency and safety of processes and equipment inside which they occur. As a result, various techniques have been developed to investigate multiphase flows. However, in the specific case of crude oil, only a few techniques have been developed and even fewer found use in industrial applications so far. Crude oil is a substance completely opaque in the visible light spectrum. However, optical spectroscopy has proven an important technique for the analysis of several substances due to the fact that the optical spectrum is unique for each substance. In this way, it is possible to investigate different substances by choosing a suitable wavelength. In the case of crude oil, it presents a high transparency in the range of mid and far infrared, which allows for the development of non-invasive measuring techniques. Along with optical spectroscopy, optical tomography has proved an alternative technique for the analysis of flow. Thus, in this work two optical tomograph in the near infrared range (950 nm) were developed in order to demonstrate the feasibility of its use in the investigation of two-phase air-water flows. Several tests of light transmittance through crude oil were conducted in mid-infrared (MIR), as well as initial test of optical tomography in crude oil. The results obtained shown that this is a viable option for flow investigation involving crude oil.